The Role of Natural Resources and the Environment in Development - Anwar Syarif; Wirda Hediyati; Reni Ria Armayani (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
This article discusses the role of natural resources and the environment in development. The development of a nation requires a basic aspect called resources, both natural resources and human resources. This article discusses several main issues, including the role of natural resources and economic development, the role of environmental economics in the analysis of environmental functions, and how the environment is related to sustainable development...